SIW Multibeam Antenna Array at 30 GHz for 5G Mobile Devices - Carla Di Paola; Kun Zhao; Shuai Zhang; Gert Frolund Pedersen (IEEE Access, 2019)
This paper presents a new phased array of substrate integrated waveguide (SIW) monopoles, characterized by simple structure, high gain, and large coverage, resulting as a good candidate for next 5G mobile handsets. The design consists of eight monopoles printed on a Rogers RO4003 substrate. In particular, four antennas are located on top of the PCB to cover the area behind the structure and four in the bottom to scan the space in front. Moreover, a high-permittivity dielectric is placed below the elements to stop the surface currents flowing along the ground plane and adjust the beam pointing. The simulations, including three different antenna array combinations, prove that the angle of over 180° can be covered with a peak gain of 12.3 dBi at 30 GHz. The prototype is fabricated, and passive measurements are performed in the anechoic chamber. The results are in accordance with the simulations and confirm the effective benefit given by the dielectric to the radiation performance of the antenna array.